THE EFFECT OF QUALITY OF WORK LIFE ON ORGANIZATIONAL COMMITMENT LECTURER IN MUHAMMADIYAH UNIVERSITY OF CIREBON - Badawi Badawi; Leisy Leisy (Value : Jurnal Manajemen dan Akuntansi, 2017)
The aim of study was to determine and analyze the influence of the quality of work life to the commitment of lecturer organization at Muhammadiyah University of Cirebon. The data of this research were obtained from the questionnaire (primary) which was disseminated on the lecturers of Universitas Muhammadiyah Cirebon as many as 51 samples from the population of 257 people. Data analysis method used in this research using simple regression showed that influenced significantly and positively because Fhitung 25.819 bigger than value Ftabel 3.18 and value of Adjusted R Square equal to3.32 or 33.2% which indicate influence of quality of work life to organizational commitment. This shows that there are still 66.8% factors or other variables that affect the organization's commitment. Inadequate and fair reward indicators are the most influential factors on organizational commitment.